Ambivalent Homoprejudice towards Gay Men: Theory Development and Validation. Issue 9 (28th July 2020) - Brooks, Ashley S.; Luyt, Russell; Zawisza, Magdalena; McDermott, Daragh T.
ABSTRACT: Myriad social groups are targets of hostile and benevolent (i.e., ambivalent) prejudice. However, prejudice toward gay men is typically conceptualized as hostile, despite the prevalence of benevolence toward gay men in popular media. This article aims to compare gay men with other targets of ambivalent prejudice (i.e., women and elderly people) and draw on the stereotype content and microaggressions literatures in order to develop a theory of ambivalent homoprejudice. The resultant framework, comprising repellent, adversarial, romanticized, and paternalistic homoprejudice was investigated using seven focus groups of heterosexuals and gay men ( N = 22), and the findings were consistent with stereotype content theory. Directions for future research into the deleterious effects of ambivalent homoprejudice and possible empowering interventions are discussed.